An application of the transtheoretical model to a case of sexual trauma in middle childhood - Vos, Sanel Marriet (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MEdPsych (Educational Psychology)--University of Stellenbosch, 2005.